Synthesis of microwave-mediated biochar-hydrogel composites for enhanced water absorbency and nitrogen release - Yudi Wu (Elsevier, 2021)
Superabsorbent hydrogels have been used to enhance water and nutrient retention in agricultural soils. However, wide applications of these polymeric soil amendments on large farms are plagued by their high costs and environmental footprints. Therefore, solutions are urgently needed in order to optimize the hydrogel application. Biochar, which is a cost-effective pyrolysis product, has been applied as soil amendments for soil fertility reservation. In this study, biochar was co-polymerized with hydrogels to explore the agronomic potentials. Biochar-hydrogel composites were synthesized through rapid mediation of microwave radiation. The physicochemical properties of these composites, such as surface functionality, thermal stability, and morphology, were characterized using various state-of-the-art analytical techniques. The discoveries in this study demonstrated that microwave irradiation could effectively facilitate structural alteration and optimize cross-linkage of biochar-hydrogel composites. Biochar-hydrogel composite (7.5% w/w biochar/composite) significantly improved swelling capacity (20.18% water was absorbed after 48 h) and optimized the nitrogen release (20.03% of nitrogen was release after 30 days) of composites. Water adsorption and nitrogen release obeyed Gallagher-Corrigan model and Korsmeyer-Peppas model, respectively. The results revealed the microwave-irradiated biochar-hydrogel composite is a promising soil amendment with regard to economic benefit and environmental footprint.